Emerging approaches to successful ecological restoration: five imperatives to guide innovation. (17th December 2017) - Matzek, Virginia; Gornish, Elise S.; Hulvey, Kristin B.
Abstract : As the science of restoration ecology and the practice of habitat restoration adapt to new sets of goals in a changing climate, we turn our attention to novel techniques and emerging approaches in the field. This special issue brings together eight papers that answer the question, "Given that we have defined our goals, can we find better ways to reach them?" From them, we derive five directives for ecologists and practitioners seeking to innovate with new methods, analyses, or applications: (1) ground the approach in ecological theory; (2) take advantage of the latest technology and models; (3) reject dogma; (4) subject the analysis to critique; and (5) be aware of time, budget, and expertise constraints faced by stakeholders and practitioners. Our five imperatives are illustrated by examples of papers from the special issue.